2020
DOI: 10.1002/agj2.20130
|View full text |Cite
|
Sign up to set email alerts
|

Early‐season grazing of native grasses offers potential profitable benefit

Abstract: A grazing trial was conducted in Mississippi during 2016 and 2017 to compare pasture, animal, and economic performance of three perennial, warm-season grass systems. Grass treatments included: (i) Argentine bahiagrass (Paspalum notatum Fluegge; BAH); (ii) KY Ecotype big bluestem (Andropogon gerardii Vitman; BBS); and (iii), KY Ecotype indiangrass [Sorghastrum nutans (L.) Nash], big bluestem and little bluestem [Schizachyrium scoparium (Michx.) Nash; MIX]. Paddocks were continuously stocked using weaned beef (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 18 publications
2
9
1
Order By: Relevance
“…CP concentration and IVTD were less than values reported for big bluestem, little bluestem, and indiangrass mixtures under clipping studies or grazing evaluations by 2-4 percentage points (Backus et al, 2017;Brazil et al, 2020;Rushing et al, 2019Rushing et al, , 2020. Differences in forage nutritive value responses among these studies and the present trial may be due to relative canopy height and stage of maturity of NWSG during the first 30 days of defoliation management.…”
Section: Forage Mass Stocking Density and Canopy Heightcontrasting
confidence: 68%
See 4 more Smart Citations
“…CP concentration and IVTD were less than values reported for big bluestem, little bluestem, and indiangrass mixtures under clipping studies or grazing evaluations by 2-4 percentage points (Backus et al, 2017;Brazil et al, 2020;Rushing et al, 2019Rushing et al, , 2020. Differences in forage nutritive value responses among these studies and the present trial may be due to relative canopy height and stage of maturity of NWSG during the first 30 days of defoliation management.…”
Section: Forage Mass Stocking Density and Canopy Heightcontrasting
confidence: 68%
“…NWSG mixtures used in the present study also supported a 30% greater animal stocking density and AUE during the first 30 days of the grazing season than the zero‐N‐input strategy. Rushing et al (2020) reported similar initial stocking densities for the first 28 days of a stocker cattle grazing trial for big bluestem, little bluestem, and indiangrass pastures fertilized at a rate of 56 kg N ha −1 in Mississippi. Pastures in their evaluation were initially stocked at a rate of 1245 and 953 kg of animal BW per hectare in Year 1 and Year 2 of the study, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations